Sovetskij sojuz :
Engl. ed.: Soviet Union. Ill. monthly (ZF 31044). - French ed.: L'Union soviètique. Revue ... (ZF 31193). - German ed.: Sowjetunion. Ill. Monatsschrift (ZF 31045). CONTINUES: S.S.S.R. na strojke. Ežemesjačnyj ... (ZF 22192).